Ethnoveterinary practice followed by Santhal tribes to treat foot and mouth diseases of livestock in Ghatshila Block, Jharkhand, India - Swain, Saujanendra; Bhattacharya, Sujoy; Chakrabarty, Suhita (Journal of Medicinal Herbs and Ethnomedicine, 2020)
An ethnoveterinary study was conducted among the Santhal tribes residing in Ghatshila block of East Singhbhum district in Jharkhand state to document the ethno-medicinal plants, those are used to treat the foot and mouth diseases of livestock. The ethnoveterinary knowledge was documented from the traditional healthcare practitioners in eight villages of the block. The study has resulted use of four plant species belonging to 4 different families to treat foot and mouth disses among livestock. Out of the four plant species, three are tress and one is shrub. The paper describes the plants used for ethno-veterinary practices to treat food and mouth diseases of livestock with botanical names, family, local names, English name, parts used, mode of preparation and administration of herbal drugs.